Migratory corridors and foraging hotspots: critical habitats identified for Mediterranean green turtles. Issue 6 (12th February 2015) - Stokes, K. L.; Broderick, A. C.; Canbolat, A. F.; Candan, O.; Fuller, W. J.; Glen, F.; Levy, Y.; Rees, A. F.; Rilov, G.; Snape, R. T.; Stott, I.; Tchernov, D.; et al.
Abstract Aim Levels of sea turtle bycatch in the Mediterranean are thought to be unsustainable. We provide a comprehensive overview of adult green turtle (Chelonia mydas) distribution during nesting, migration and foraging phases, highlighting transitory as well as residential areas of high use to facilitate adequate protection for this long‐lived, migratory species. Location Mediterranean Sea. Methods Thirty‐four females were satellite tracked from breeding grounds in the four countries with major nesting (Cyprus, Turkey, Israel and Syria) for a total of 8521 (mean: 251) tracking days in a collaborative effort to summarize the most comprehensive set of distribution data thus far assembled for this species in the Mediterranean. Results Ten foraging grounds are identified, with two major hotspots in Libya accounting for >50% of turtles tracked to conclusive endpoints. The coastlines of Egypt and Libya contain high densities of migrating turtles following the nesting season, particularly July–September, and likely also pre‐nesting (April–June). A high‐use seasonal pelagic corridor running south‐west from Turkey and Cyprus to Egypt is also evident, used by >50% of all tracked turtles. Main conclusions Bycatch levels and mortality rates for the key foraging areas and high‐density seasonal pathways identified here are largely unknown and should be investigated as a priority. We recommend that the Gulf of Sirte in Libya be explored as a potential biodiversity hotspot and considered for proposal as a marine protected area (MPA). Green turtle fidelity to nesting beaches, foraging areas and migratory pathways renders them vulnerable to localized threats but enables targeted mitigation measures and protection.